Complementary livelihood capital as a means to enhance adaptive capacity: A case of the Loess Plateau, China. (November 2017) - Li, Mengping; Huo, Xuexi; Peng, Changhui; Qiu, Huanguang; Shangguan, Zhouping; Chang, Cheng; Huai, Jianjun
Highlights: We assessed the adaptive capacity of apple farmers to drought events in the Loess Plateau, China. The complementarity-substitution exists between social, human, physical, natural, and financial capitals. It is the overall product of these complementary indicators capital that increases adaptive capacity. A substitutive-complementary approach helps to understand the role of livelihood capital in increasing adaptive capacity. Abstract: The sustainable livelihoods framework (SLF) highlights the positive relationship between a broad portfolio of household livelihood capitals and adaptive capacity to climate change. However, the SLF overlooks the interactions and transformations that occur between different types of capital. To test our hypothesis that complementarity-substitution exists between the five livelihood capitals, and that only increasing complementary capital can improve adaptive capacity, we assessed the adaptive capacity of apple farmers to drought events in the Loess Plateau, China. This was done through a substitutive-complementary analysis of the relationships between social, human, physical, natural, and financial capital. Using Pearson's correlation analysis, we tested the impact of 13 livelihood capital indicators on farmers' adaptive capacity. We found that some forms of capital have a substitutive effect, some have a complementary effect, and others have both. It is the overall product of these complementary indicators that increases adaptive capacity. We conclude that a substitutive-complementary approach can enhance our understanding of the role of livelihood capital in reducing farmers' vulnerability and strengthen approaches to increasing adaptive capacity.